Organizational Citizenship Behavior in Relation to Job Satisfaction among Employees of Karya Anugerah Education Foundation - Hartini, Sri; Vincent, Vincent; Tanaka, Valencia; Monica Meyer, Sharon; Ngayomi Yudha Wastuti, Sri (Riviera Publishing, 2023)
This research aims to determine and analyze the relationship between job satisfaction and Organizational Citizenship Behavior (OCB). This quantitative method research involved a sample of 95 employees of the Karya Anugerah Education Foundation from a total population of 127 employees using the Isaac and Michael formula with an error rate of 5%. The purposive sampling method was used to obtain data from this analysis. In this research, the Pearson product-moment correlation test and other statistical analyzes were carried out using SPSS for Windows version 25.0. There is a correlation coefficient of 0.621 and Sig 0.000 with a positive value. Where there is a correlation coefficient of 0.621 and Sig 0.000 with a positive value. The research hypothesis shows that there is a positive relationship between these two variables. The assumption test shows that OCB is greater when the level of job satisfaction is higher. Conversely, the lower the level of job satisfaction, the lower the OCB.